1990
DOI: 10.1063/1.103487
|View full text |Cite
|
Sign up to set email alerts
|

Lateral quantum well wires fabricated by selective metalorganic chemical vapor deposition

Abstract: GaAs quantum wires of a new type are fabricated on {1̄10} crystallographic facets perpendicular to the (1̄1̄1̄)B substrates by selective area growth using metalorganic chemical vapor deposition. First, rectangular-shaped AlGaAs layers are grown on a SiO2 stripe-masked GaAs (1̄1̄1̄)B substrate at a high growth temperature. Next, n-AlGaAs/GaAs modulation-doped structures are laterally grown on {1̄10} sidewalls at a low growth temperature. The channel width of the one-dimensional electron gas can be exactly contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Recently, nanostructures such as quantum dots [1,2] and quantum wires [3,4] have been fabricated by combining the bottom-up crystal growth techniques and top-down microand nanofabrication techniques by using molecular beam epitaxy (MBE) and metal organic vapor phase epitaxy (MOVPE). Among these, area selective epitaxy (ASE) is one of the most promising methods to fabricate semiconductor micro-and nanostructures because it produces less damage in the substrate than the direct machining techniques such as reactive ion etching (RIE) and focused ion beam implantation (FIB) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nanostructures such as quantum dots [1,2] and quantum wires [3,4] have been fabricated by combining the bottom-up crystal growth techniques and top-down microand nanofabrication techniques by using molecular beam epitaxy (MBE) and metal organic vapor phase epitaxy (MOVPE). Among these, area selective epitaxy (ASE) is one of the most promising methods to fabricate semiconductor micro-and nanostructures because it produces less damage in the substrate than the direct machining techniques such as reactive ion etching (RIE) and focused ion beam implantation (FIB) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In this mechanism, {-110} vertical facets can appear on a (111)B-oriented surface under specific growth conditions. Fukui et al demonstrated the formation of rectangular-shaped GaAs wire surrounded by the {-110} vertical facets on a GaAs(111)B substrate [21].…”
Section: A Direct Integration Of Iii-v Nws On Si/gementioning
confidence: 99%
“…[1][2][3][4][5][6] Metalorganic vapor phase epitaxy ͑MOVPE͒ of ternary alloy layers on V-groove patterned substrates is known to lead nonuniformity of alloy composition driven by the preferential diffusion of one of the constituent materials to the bottom of the V-groove and/or the orientation-dependent difference of incorporation rate among the constituent materials. This nonuniformity is particularly pronounced in the case of Al x Ga 1Ϫx As/V-grooved GaAs since Ga adatoms are much more mobile than Al toward the bottom of the V-groove.…”
mentioning
confidence: 99%